Chronic biological false-positive reactions to serological tests for syphilis in blood donors - Garner, M. F. (1970)
Problem sera from 375 blood donors were investigated for biological false-positive reactions to serological tests for syphilis. Problem sera are those sera in which submitting laboratories have found a reactive result to a screening test for syphilis. On each serum a cardiolipin Wassermann reaction, a Venereal Disease Research Laboratory test, a Reiter protein-complement fixation test, a Treponema pallidum immobilization test, and a fluorescent treponemal antibody absorption test were performed. Of the sera 49·9% were found to be non-reactive in all five tests, 28·8% gave results indicating a diagnosis of syphilis, and 21·3% showed biological false-positive reactions. There were 80 sera from blood donors which gave biological false-positive reactions. A further specimen of serum from 67 of these donors was tested after an interval of a minimum of six months. Sixty-six of the sera showed chronic biological false-positive reactions. Some donors were only found reactive for the first time after they had given very many donations of blood. It is concluded that sudden blood loss, as in blood donation, appears to stimulate the production of excess reagin in certain individuals, causing a chronic biological false positive reaction to serological tests for syphilis. This may only appear after several blood donations have been made.